PENGATURAN HUKUM TERHADAP PEREMPUAN PELAKU TINDAK PIDANA PERKOSAAN - Lukman Hakim; Endang Prasetyawati; Otto Yudianto (Jurnal Akrab Juara, 2019)
Crime is a form of deviant behavior (crime) that is always there and is inherent in every form of society. One form of crime that occurs at this time is the act of decency or rape. "Rape is a crime that has a high level and invites the growth of fear of creme." Perpetrators can be anyone, as well as victims can be women or men. The crime of rape committed by women until now there are no rules governing it. So it is important to be investigated, what is the urgency of legal arrangements for women perpetrators of rape. By using normative juridical research methods, based on legal principles and legislation relating to criminal law, specifically rape crime. If it is not immediately regulated, then law enforcement against women perpetrators of rape can not be carried out, because it is clearly stated in Article 1 paragraph (1) of the Criminal Code "An act cannot be convicted, except based on the strength of existing criminal law provisions".